Epistimologi Politik: Studi Atas Politik Hukum Undang-Undang Perbankan No. 10/1998 - Zainal Said; Irwan Abdullah; Lasiyo Lasiyo (Jurnal Studi Pemerintahan, 2012)
Legal and political system is a subsystem in the community. Each perform a specific function to move the social system as a whole. A rill, a national banking law norms contained in Law no. 7/1992 concerning Banking as amended by Law no. 10/1998 provide less public protection arrangements (social protection) than in community settings (social deregulation). The Law. 7/1992 on banking, as amended by Law No. 10/1998 which does not restrict the ownership of commercial banks. In a company where there are differences in ownership of company shares a number of very big difference, it will be found the majority shareholder in one hand and minority shareholders, on the other by differences in the number of voting rights is striking. Lessons of the past shows that the majority principle causes ¬'s minority shareholders are in a position of powerlessness and disadvantage in enforcing their interests. Legal position of minority shareholders who number more weak and unable to deal with actions that harm the directors or commissioners of the company, it is caused by the position of the majority shareholder of which is identical with the company's second organ, both physically and interests.